Effects of dietary zinc supplementation during a forced molt on subsequent hen performance and egg quality. - Ahmed, Rebwar Mohamad; Ali, Khasraw Abdulla (Sulaimani Journal for Pure and Applied Sciences, 2015)
A total of 200 Hy- Line Brown commercial layer hens (64) weeks of age, were used in this study to investigate the impacts of different dietary zinc supplementation during a forced molt on subsequent hen performance and egg quality. The hens were randomly divided into (5) treatment groups of 40 hens each treatment. There were four replicate cages per treatment. The hens in the treatment 1 (control) were fed a layer ration containing 0 ppm ZnO, water and feed were provided ad libitum and received 16 hours of light/day, treatment (2) were fed a layer ration containing 28000 ppm Zn as zinc oxide for 11 days, treatment (3) 37000 ppm ZnO for 9 days, treatment (4) 46000 ppm ZnO for 7 days, and treatment (5)on-again, off-again program (ON-OFF).The experimental period was divided into seven periods (1) 64-66, (2) 67-69, (3) 70-72, (4) 73-75, (5) 76- 78, (6) 79-81, (7) 82-84 weeks. The results indicated that different levels of dietary zinc were improved Hen Day (H.D) egg production and egg weight at periods 70-72, 73-75, 76-78, 79-81, 82-84 weeks, except treatment 37000 ppm ZnO in period 70-72 was reduced in both egg production and egg weight, yolk and white weight improved also in these five periods above, feed intake was improved in two periods 70-72 and 73-75 weeks, feed conversion ratio was decreased in two periods 73-75 and 76-78 weeks, compared to both control and ON-OFF program. Haugh unit was improved in dietary zinc treatments and ON-OFF program in all periods except period 64-66 weeks compared to control. The percentage of weight loss was increased in the period 64-67 weeks for all treatments except control. Different dietary zinc supplementation was increased the concentration of zinc in yolk from 10.20 ppm (control) to 32.84, 29.61 and 51.08 and, white from 3.50 ppm (control) to 5.96, 5.90 and 6.37 ppm for 28000, 37000 and 46000 ppm during fed them with Zn for 11, 9 and 7 days, respectively, but the concentration of zinc in yolk and white was reduced week by week after following the refeeding of a control diet and was normally by week 6.
Keywords: Layer hen; forced molting; zinc; egg quality